2001
DOI: 10.1143/jjap.40.l552
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Nd:Y3Al5O12 Ceramic Laser

Abstract: A highly efficient laser diode end-pumped polycrystalline 1% Nd:Y3Al5O12 (Nd:YAG) ceramic laser has been developed. It is comparable to a Nd:YAG single crystal laser in terms of efficiency. With 883 mW pumping, CW laser output of 499 mW at 1064 nm has been obtained, which corresponds to an optical-to-optical efficiency of 56.5%. The threshold is only 22 mW for a R=97% output coupler. Passively Q-switched operation has also been demonstrated using a Cr4+:YAG single crystal as a saturable absorber.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(27 citation statements)
references
References 10 publications
0
26
0
1
Order By: Relevance
“…9(b)], which can be attributed to the transition from 4 I 9/2 to 4 F 5/2 . This wavelength is commonly used as pumping wavelength to generate 1064 nm laser output, [19][20][21][22] corresponding to the excited radiation from 4 F 3/2 to 4 I 11/2 . Moreover, for both composite ceramics, it was found that the transmittance can be increased by annealing treatment, due to the elimination of defects and lattice stress.…”
Section: Structural and Optical Analysismentioning
confidence: 99%
“…9(b)], which can be attributed to the transition from 4 I 9/2 to 4 F 5/2 . This wavelength is commonly used as pumping wavelength to generate 1064 nm laser output, [19][20][21][22] corresponding to the excited radiation from 4 F 3/2 to 4 I 11/2 . Moreover, for both composite ceramics, it was found that the transmittance can be increased by annealing treatment, due to the elimination of defects and lattice stress.…”
Section: Structural and Optical Analysismentioning
confidence: 99%
“…Transparent laser ceramics [6,[13][14][15][16] fabricated by the vacuum sintering technique and nanocrystalline technology [17] have been proven to be potential replacements for counterpart single crystals because they have several remarkable advantages compared with single-crystal laser materials, such as high concentration and easy fabrication of large-size ceramics samples, multilayer and multifunctional ceramics laser materials [18,19]. Rare earths ions doped Lu 2 O 3 , Sc 2 O 3 , and Y 2 O 3 oxides ceramics have been developed and their mechanical and optical properties are reported recently [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…The recent advent of transparent polycrystalline YAG lasers that outperform single-crystal YAG lasers has intensified interest in the development of very fine YAG particles that are easily sintered to full density and transparency. [11,12] We report here efforts to produce nanosized Y 3 Al 5 O 12 powders for this purpose that result in a new phase with higher densities than YAG and sinter to full density at relatively low temperatures. We recently described a new method of producing large quantities of single and mixed-metal oxide nanopowders with exceptional control of composition based on liquid-feed flame spray pyrolysis.…”
mentioning
confidence: 99%